Effect of rainfall variability on tea growing in Kyamuhunga tea estate. A cross-sectional study. - Twinamatsiko, Linard; Nagawa, Goretty; Kazibwe, Assoc. Prof. Francis (Student's Journal of Health Research Africa, 2026)
Background Water availability is the most important factor for crop productivity in rain-fed agriculture. This study examines how changes in rainfall affect tea growing. Methods This study adopts a cross-sectional research design to gather data. It employed quantitative approaches to provide a comprehensive understanding of the research topic. The research design includes surveys, interviews, and observations to collect primary data, as well as the review of existing literature to supplement the findings. Results The key findings reveal that rainfall variability had a significant positive influence on tea growing since the p-value is less than 0.05. The Pearson correlation coefficient (r=.566) shows a positive, moderately significant influence of rainfall variability on tea growing. This implies that any positive changes in rainfall variability led to a positive change in tea growing in the Kyamuhunga Tea estate. The results also indicate that a unit increase in rainfall variability will result in a 0.321 increase in tea growing (B=.321, p=0.000 < 0.05). Conclusions Rainfall variability had a significant positive influence on tea growing, and there was a moderate, significant influence of rainfall variability on tea growing. This implies that any positive changes in rainfall variability led to a positive change in tea growing in the Kyamuhunga Tea estate. Recommendation The study recommends that, for tea farmers, considering implementing irrigation systems to supplement water during periods of low rainfall. Tea growers should collaborate with researchers and institutions to stay updated on the latest techniques and practices.